1987
DOI: 10.1126/science.2890209
|View full text |Cite
|
Sign up to set email alerts
|

A DNA Segment Encoding Two Genes Very Tightly Linked to Huntington's Disease

Abstract: The discovery of D4S10, an anonymous DNA marker genetically linked to Huntington's disease (HD), introduced the capacity for limited presymptomatic diagnosis in this late-onset neurodegenerative disorder and raised the hope of cloning and characterizing the defect based on its chromosomal location. Progress on both fronts has been limited by the absence of additional DNA markers closer to the HD gene. An anonymous DNA locus, D4S43, has now been found that shows extremely tight linkage to HD. Like the disease g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
2

Year Published

1988
1988
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(27 citation statements)
references
References 10 publications
1
24
0
2
Order By: Relevance
“…D4S43 is a polymorphic locus identified in humans that is closely linked to the Huntington's disease gene (HD) on human chromosome 4p (Gilliam et al 1987;S.V. Cheng et al, in prep.).…”
Section: Discussionmentioning
confidence: 99%
“…D4S43 is a polymorphic locus identified in humans that is closely linked to the Huntington's disease gene (HD) on human chromosome 4p (Gilliam et al 1987;S.V. Cheng et al, in prep.).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we conclude that genes that contribute to the WHS phenotype reside in the interval distal to D4S43 and proximal to D4S168. This localization effectively eliminates several genes (MYL5, ZNF141, PDE␤, and IDUA) mapped to 4p16.3 previously suggested as having a role in the etiology of WHS.Several potentially expressed sequences have been found throughout the WHSCR but these have not been studied in detail [Gilliam et al, 1987;John et al, 1994;Rommens et al, 1993;Snell et al, 1993]. The exception is the FGFR3 gene, located near the distal end of the refined WHSCR, FGFR3 has been studied both for its role in a number of growth related disorders [Bellus et al, 1995;Meyers et al, 1995;Shiang et al, 1994;Tavormina et al, 1995].…”
mentioning
confidence: 94%
“…Owing to the abundant cloned resources from this region of the genome, a large number of potential coding sequences were identified [Gilliam et al, 1987;John et al, 1994;Rommens et al, 1993;Snell et al, 1993]. Overall, the region appears to be gene dense.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic distance between D4SJ0 and HD is estimated at 3 centimorgans (cM), with 95% confidence limits of0.8-6 cM (8). On the average, 1 cM of genetic distance corresponds to p1000 kilobases (kb) of physical distance (9), but the rarity of DNA sequences in a chromosome 4 library that map distal to D4S10 (10,11) and the observed increase in chiasma formation near the telomeres of most autosomes (12) suggest that the physical distance between D4SJO and HD might well be <3000 kb.…”
mentioning
confidence: 99%
“…Very recently, another DNA marker, D4S43, has been identified that maps distal to D4SJO and is therefore either closer to HD on the same side or is a flanking marker (11). Its distance from HD is estimated to be 0-1.5 cM.…”
mentioning
confidence: 99%